Латышскіе отрывки [Латышские отрывки] - Wolter, Eduard; Вольтер, Э. А. (Типография Императорской Академии наук, 1907)
"Отдѣльный оттискъ изъ Извѣстій Отдѣленія русскаго языка и словесновти Императорской Академіи Наукъ, т. XII (1907 г.), 3-я кн., стр. 163-175".
Латышские отрывки
Keywords: Research Subject Categories::HUMANITIES and RELIGION::Languages and linguistics::Other languages::Baltic languages; Research Subject Categories::LAW/JURISPRUDENCE; Latviešu valoda; Juridiskā latviešu valoda; Latviešu rakstu valoda, juridiskā; Tiesu sēžu protokoli, 17. gs. - Latvija; Latvian language; Legal Latvian language; Court records, 17th century - Latvia; Латышский язык; Юридический латышский язык